Recurrent somatic mutations of FAT family cadherins induce an aggressive phenotype and poor prognosis in anaplastic large cell lymphoma - Villa, Matteo; Sharma, Geeta G; Malighetti, Federica; Mauri, Mario; Arosio, Giulia; Cordani, Nicoletta; Lobello, Cosimo; Larose, Hugo; Pirola, Alessandra; D'Aliberti, Deborah; Massimino, Luca; Criscuolo, Lucrezia; et al. (British journal of cancer, 2024)
BACKGROUND: Anaplastic Large Cell Lymphoma (ALCL) is a rare and aggressive T-cell lymphoma, classified into ALK-positive and ALK-negative subtypes, based on the presence of chromosomal translocations involving the ALK gene. The current standard of treatment for ALCL is polychemotherapy, with a high overall survival rate. However, a subset of patients does not respond to or develops resistance to these therapies, posing a serious challenge for clinicians. Recent targeted treatments such as ALK kinase inhibitors and anti-CD30 antibody-drug conjugates have shown promise but, for a fraction of patients, the prognosis is still unsatisfactory. METHODS: We investigated the genetic landscape of ALK + ALCL by whole-exome sequencing; recurring mutations were characterized in vitro and in vivo using transduced ALCL cellular models. RESULTS: Recurrent mutations in FAT family genes and the transcription factor RUNX1T1 were found. These mutations induced changes in ALCL cells morphology, growth, and migration, shedding light on potential factors contributing to treatment resistance. In particular, FAT4 silencing in ALCL cells activated the β-catenin and YAP1 pathways, which play crucial roles in tumor growth, and conferred resistance to chemotherapy. Furthermore, STAT1 and STAT3 were hyper-activated in these cells. Gene expression profiling showed global changes in pathways related to cell adhesion, cytoskeletal organization, and oncogenic signaling. Notably, FAT mutations associated with poor outcome in patients. CONCLUSIONS: These findings provide novel insights into the molecular portrait of ALCL, that could help improve treatment strategies and the prognosis for ALCL patients.
Keywords: fenotyp; zvířata; Exome Sequencing; prognóza; Animals; lidé; Prognosis; Mutation; Mice; kadheriny; mutace; sekvenování exomu; Lymphoma, Large-Cell, Anaplastic; Humans; myši; nádorové buněčné linie; anaplastický velkobuněčný lymfom; Cadherins; Phenotype; Cell Line, Tumor